Gastric Medullary Carcinoma: A Rare Case Report - Ferit Aslan; Fisun Ardıç Yükrük; Fatma Buğdaycı Başal; Ayşe Durnalı (Case Reports in Oncological Medicine)
A case of 64-year-old female patient with early stage gastric medullary carcinoma has been presented, along with a review of the literature.